Wound healing by brand new product - Lee Jae Bong; Cho Seong Keun; Lim Jong So; Kang Kyung Soo (International Journal of Veterinary Science and Research - Peertechz Publications, 2023)
Eggshell Membrane (ESM) has been used as an alternative natural bandage to cure wounds and is available in large quantities from egg industries. This study is based on the use of natural resources for skin tissue reconstruction. It needs to understand regeneration of tissue with Extracellular Matrix (ECM).  Wound healing is a complicated and continuous recovery process of damaged tissues by replacing dysfunctional injured cellular structures. The wound healing process recruits some different phases: the first phase for hemostasis, the second phase for inflammation, the third phase for proliferation, and last phases for maturation/tissue remodeling. Each process needs an appropriate surrounding to achieve accelerated healing. Because the skin is in contact with the outside, injuries occur and therefore the surface is often injured. Due to the different types of wounds, as well as the advancement in medical technology, various products have been developed to repair different skin lesions.  We investigate the wound healing effects which are measured by dividing into the Exture® group, the commercially available wound dressing group (positive control), and the untreated group (negative control). We induced wounds and measured the healing process for 20 days for a comparison experiment of collagen membrane wound healing.  As for the wound, the decrease in wound area using external photographs, the healing process within the tissue, and the immune response were measured through hematology analysis. We confirmed some differences through comparison of blood cell analysis and wound healing process but did not find statistical significance. There was no significant difference between treated collagen wound dressing film and commercial wound dressing film.  Thus, this study reveals that the possibility of use natural source-based wound healing products brings sufficient wound healing results.